Reading Hegel's Phenomenology - Russon, John (Indiana University Press, 2004)
In "Reading Hegel's Phenomenology", John Russon uses the theme of reading to clarify the methods, premises, evidence, reasoning, and conclusions developed in Hegel's seminal text. Russon's approach facilitates comparing major sections and movements of the text, and demonstrates that each section of "Phenomenology of Spirit" stands independently in its focus on the themes of human experience. Along the way, Russon considers the rich relevance of Hegel's philosophy to understanding other key Western philosophers, such as Aristotle, Descartes, Kant, Husserl, Heidegger, and Derrida. The major themes include language, embodiment, desire, conscience, forgiveness, scepticism, law, ritual, multiculturalism, existentialism, deconstruction, and absolute knowing. An important companion to contemporary Hegel studies, this book will be of interest to all students of Hegel's philosophy.